PEMBERDAYAAN KOMUNITAS PEMUDA: MENUJU PALANGKA RAYA SEBAGAI IBUKOTA PEMERINTAHAN REPUBLIK INDONESIA - Suprayitno, Suprayitno; Silalahi, Juli Natalia; Pratiwi, Putri Fransiska Purnama (Jurusan Ilmu Administrasi Publik, Universitas Lampung, 2019)
The article aimed to analyze and identify the readiness of the Palangka Raya city to be the Administrative Capital City of the Republic of Indonesia. An indicator is from the aspect of Youth readiness in the City of Palangka Raya in welcoming the transfer of the administrative capital city. As an important aspect in preparing the Palangka Raya city as the Capital of the future Government is the readiness of youth in the Palangka Raya itself in welcoming the transfer of the administrative capital city from Jakarta to Palangka Raya. Youth, in reality, is a pioneer of any changes occurring throughout the history of the Indonesian. The roles of youth always start from the National Awakening on 1908, the Youth Oath on 1928, the Independence Revolution on 1945, the Proclamation of Independence on 1945, and the Reformation Movement on 1998. Based on history on behalf of the Youth has sensitivity to the problems faced by the nation. Currently, there is a positive trend related to Youth activities in Palangka Raya. Today, there are a lot of youth communities in the Palangka Raya that are formed by young people on the basis of social awareness, voluntary and non-profit oriented aiming to improve competence. There needs a collaboration between the local government and the youth community aiming to invite more youth in Palangka Raya who are creative in an effort in welcoming the transfer of the administrative capital city of Republic of Indonesia, from Jakarta to Palangka Raya city.